Analisis Pengaruh Tingkat Inflasi, Jumlah Nasabah, dan Pendapatan Gadai Syariah Terhadap Penyaluran Kredit Gadai Syariah (Rahn) (Studi Kasus pada Pegadaian Syariah Periode 2010-2019) - Sutan Emir Hidayat; Oktaviany, Mega; Indah Royani (Universitas Islam Negeri Alauddin Makassar, 2022)
This research aims to analyze the influence of inflation rate, number of customers, and Sharia pawn income on the distribution of Sharia pawn credit (rahn) (case study at Pegadaian Syariah from 2010 to 2019). This study uses secondary data with time series obtained from the Annual Report of PT Pegadaian (persero) and the Bank Indonesia website from 2010 to 2019 and uses multiple linear regression methods assisted by the Microsoft Excel 2010 program and SPSS 24 software. The results of the study partially show that the inflation rate does not have a significant effect on the distribution of Sharia pawn credit (rahn) with a sig value of 0.831 > 0.05. Meanwhile, the number of customers also does not have a significant effect with a sig value of 0.798 > 0.05, and Sharia pawn income has a significant positive effect with a sig value of 0.000 < 0.05. Simultaneously, the results of this study show that the inflation rate, number of customers, and Sharia pawn income have a significant effect on the distribution of Sharia pawn credit (rahn) with a sig value of 0.000 < 0.05.